Evaluation of Thematic Academy (TA) Digital Talent Development Program Using the CIPP Model - Agung Rahmat Dwiardi; Muhamad Yopan (SOSIOEDUKASI, 2025)
The Human Resource Development (HRD) program at the Ministry of Communication and Informatics through the Thematic Academy training program has a strategic goal of improving the competence and skills of national human resources in the ICT sector. This HR development policy is part of the government's efforts to support the acceleration of digital transformation. This study was conducted to evaluate the Thematic Academy program using the Context, Input, Process, and Product (CIPP) evaluation model. Data collection methods in this study involved surveys of 249 respondents. Descriptive analysis was conducted after data processing, validity testing, and reliability testing. The study results indicate that the performance achievement of the Thematic Academy program has exceeded the set target. However, based on the CIPP model evaluation, several aspects received a "sufficient" rating, namely context, process, and product. Meanwhile, only the input aspect received a "good" rating. Therefore, although this program has been running well, it is essential to pay attention to these aspects to further improve its quality.